Uncovering theology : the depth, reach and utility of Australian theological education. - Sherlock, Charles (ATF Press, 2009)
Report of a project designed to provide a detailed, evidence-based portrait of Australian theological education in order to improve learning and teaching within it. The project also: articulated the complementary roles of the two peak bodies in Australian theological education, The Council of Deans of Theology, and the Australian and New Zealand Society for Theological Studies; developed common benchmarks across Australian theological education; and identified the need to foster the general spirit of co-operation and collaboration in Australian theological education. [p.17, ed]